Downregulation of Long Noncoding RNA LUCAT1 Suppresses the Migration and Invasion of Bladder Cancer by Targeting miR-181c-5p. (17th November 2020) - Chen, Yifan; Zhang, Wentao; Shen, Liliang; Kadier, Aimaitiaji; Huang, Jianhua; Wang, Ruiliang; Wu, Pengfei; Yao, Xudong
Abstract : Purpose . The long noncoding RNA LUCAT1 (lung cancer-associated transcript 1) has been reported to be highly expressed in bladder cancer samples, but its role and molecular mechanisms need to be elucidated. Methods . Bioinformatics methods show that miR-181c-5p is a target of LUCAT1. Here, we aimed to reveal whether LUCAT1 participates in the development of bladder cancer via targeting miR-181c-5p. The expression levels of LUCAT1 and miR-181c-5p were detected by RT-PCR technology in bladder cells and tissues. The effects of the LUCAT1/miR-181c-5p axis on cell proliferation, migration, invasion, and apoptosis were tested by CCK-8, wound healing, Transwell chambers, and flow cytometry assays. The expressions of apoptosis/migration-related proteins were detected by western blotting assays. Results . The results demonstrated that LUCAT1 was overexpressed in bladder cancer tissue and cells, while miR-181c-5p showed a low expression pattern as compared to normal bladder cells and tissues. Cell proliferation, migration, and invasion capacities were significantly impaired, and cell apoptosis was enhanced when LUCAT1 was silenced in UM-UC-3 and T24 cell lines, but this effect was abolished by miR-181c-5p downregulation. In addition, miR-181c-5p downregulation impaired LUCAT1 downregulation which mediated the decreased expressions of Bcl2 and N-cadherin and the increased expressions of Bax and E-cadherin. Moreover, we found that KRAS was a direct target of miR-181c-5p and was under the positive regulation of LUCAT1. Conclusion . Collectively, this study reveals that knockdown of LUCAT1 inhibits the migration and invasion of bladder cancer cells in a miR-181c-5p-dependent manner, which may be related to KRAS downregulation.